Interpretation of massive sandstones in ephemeral fluvial settings: A case study from the Upper Candelária Sequence (Upper Triassic, Paraná Basin, Brazil). (January 2018) - Horn, Bruno Ludovico Dihl; Goldberg, Karin; Schultz, Cesar Leandro
Abstract: Ephemeral rivers display a wide range of upper- and lower-flow regime structures due to great flow-velocity changes during the floods. The development of flow structures in these setting is yet to be understood, especially in the formation of thick, massive sandstones. The Upper Triassic of Southern Gondwana was marked by a climate with great seasonal changes, yet there is no description of river systems with seasonal characteristics in Southern Gondwana. This work aims to characterize a ephemeral alluvial system of the Upper Triassic of the Paraná Basin. The characteristics of the deposits are discussed in terms of depositional processes through comparison with similar deposits from literature, flow characteristics and depositional signatures compared to flume experiments. The alluvial system is divided in four facies associations: (1) channels with wanning fill, characterized by low width/thickness ratio, tabular bodies, scour-and-fill structures with upper- and lower-flow regime bedforms; (2) channels with massive fill, characterized by low w/t ratio, sheet-like bodies, scour-and-fill structures with massive sandstones; (3) proximal sheetfloods, characterized by moderate w/t ratio, sheet-like bodies with upper- and lower-flow regime bedforms and (4) distal sheetfloods, characterized by high w/t ratio, sheet-like bodies with lower-flow regime bedforms. Evidence for the seasonal reactivation of the riverine system includes the scarcity of well-developed macroforms and presence of in-channel mudstones, thick intraformational conglomerates, and the occurrence of well- and poorly-preserved vertebrate bones in the same beds. The predominantly massive sandstones indicate deposition from a hyperconcentrated flow during abrupt changes in flow speed, caused by de-confinement or channel avulsion, whereas turbulent portions of the flow formed the upper- and lower-flow regime bedforms after the deposition of the massive layers. The upper portion of the Candelária Sequence records a good example of strongly ephemeral alluvial systems, where the predominance of massive sandstones is a particular characteristic. Highlights: Fluvial deposits dominated by massive sandstones described for Candelária Sequence. A model for the formation of massive sandstones in this kind of system is proposed. Paleoclimatic and paleontological data are utilized to support the model.